Priming Soybean cv. Primus Leads to Successful Systemic Defense Against the Root-Lesion Nematode, Pratylenchus penetrans - Adss, Shimaa; Liu, Benye; Beerhues, Ludger; Hahn, Volker; Heuer, Holger; Elhady, Ahmed (Frontiers in Plant Science, 2021)
Abstract Root lesion nematodes, Pratylenchus penetrans, are major pests of legumes with little options for their control. We aimed to prime soybean cv. Primus seedlings to improve basic defence against these nematodes by root application of N-3-oxo-tetradecanoyl-L-homoserine lactone (oxo-C14-HSL). The invasion of soybean roots by P. penetrans was significantly reduced in plants that were pre-treated with the oxo-C14-HSL producing rhizobacterium Ensifer meliloti strain ExpR+, compared to non-inoculated plants or plants inoculated with the nearly isogenic strain E. meliloti AttM with plasmid-mediated oxo-C14-HSL degradation. The nematodes were more clustered in the root tissues of plants treated with the AttM strain or the control compared to roots treated with the ExpR+ strain. In split-root systems primed on one side with strain ExpR+, root invasion was reduced on the opposite side compared to non-primed plants indicating a systemic plant response to oxo-C14-HSL. No additional local effect was detected, when inoculating nematodes on the ExpR+ primed side. Removal of oxo-C14-HSL after root exposure resulted in reduced root invasion compared to non-primed plants when the nematodes were added 3, 7, or 15 days later. Thus, probably the plant memorized the priming stimulus. Similarly, the plants were primed by compounds released from the surface of the nematodes. HPLC analysis of the root extracts of oxo-C14-HSL treated and untreated plants revealed that priming resulted in enhanced phytoalexin synthesis upon P. penetrans challenge. Without root invading nematodes, the phytoalexin concentrations of primed and non-primed plants did not significantly differ, indicating that priming did not lead to a persistently increased stress level of the plants. Upon nematode invasion, the phytoalexins coumestrol, genistein, and glyceollin increased in concentration in the roots compared to control plants without nematodes. Glyceollin synthesis was significantly more triggered by nematodes in primed plants compared to non-primed plants. The results indicated that the priming of soybean plants led to a more rapid and strong defence induction upon root invasion of nematodes.